Taking it with you when you go: The Monumentality of Death and Everlasting Life in Artist-built Environments - Farb Hernández, Jo (Eikón / Imago, 2021)
An introduction to the genre of monumental gravesites and tombs conceived and built by self-taught creators of art environments for their own eventual personal use, illustrated through a presentation of the constructed final resting places of six artist-builders. This article distinguishes these unique constructions from more traditional gravesites that evidence communally recognized motifs and symbols with forms and components that fall within standard parameters. In contrast to these more typical manifestations, the studied genre is both much less widespread and much more idiosyncratic and reveals a more personal expression of what the builder hopes to encounter in the “beyond,” as well as how they want to interpret what they leave behind. Because the majority of these structures are installed in private spaces, studies of heritage tombs and cemeteries have little resonance. Likewise, due to the lack of connection or communication between these artists, it is impossible to posit a thread of confluence that unites these structures in a way that would provide a more generalized understanding of the meaning of life and death or the import of one’s journey through the world held by art-environment builders. It is, however, safe to assume that one of their ultimate goals is to have their physical works function as a trigger to bring them a measure of immortality.